Decoupling the EU ETS from subsidized renewables and other demand side effects: Lessons from the impact of the EU ETS on CO₂ emissions in the German electricity sector - Sebastian Schäfer (Philipps-University Marburg, School of Business and Economics, 2018)
This paper analyzes the impact of the EU ETS on CO₂ reduction in the German electricity sector. We find an ETS-induced emission abatement which is not exceeding 6% of total emissions with a maximum already in 2010. Thereafter the ETS has not induced additional reductions. This outcome is sub-optimal. It corresponds to the recent debate about sub-optimal performance of the EU ETS caused by excessive allowances. Following up on this we develop a unilateral flexible cap to eliminate demand side effects which lead to excessive allowances. The unilateral flexible cap is based on emission intensities. Using the works of Newell and Pizer (2008); Sue Wing et al. (2009) we prove in a first step that an intensity-based emission cap is advantageous in the German electricity sector when compared to an absolute cap. An ex-post analysis shows that the amount of excessive allowances resulting from the economic crisis during the second trading period could have been significantly lowered with a unilateral flexible cap. This approach also decouples the EU ETS from a simultaneous promotion of renewable energy.
Keywords: Q41; Q42; Q48; Q54; 330; Decoupling Overlapping Regulations; Promotion of Renewable Energy; Emissions Trading; Intensity Standard